Molecular genetic evaluation of Cichorium endivia L. as an anticancer agent against colorectal cancer - Elsayed E Hafez,; Effat Badr,; Yasser Mabrouk,; Mohammed El-Seehy,; Sarah Aggag, (International Journal of Phytomedicine, 2016)
Medicinal plants confer protective effects against a wide range of cancers including colon cancer. Cichorium endivia L. has many biological activities and functions, such as anti-inflammation and hepatoprotective effects. This activity is mainly due to its high levels of antioxidant compounds. The effect of cichorium extract and fluorouracil (5-FU) against colorectal cancer (CRC) induced by 1, 2- Dimethyl hydrazine (DMH) was examined in male albino mice. Where, different doses of cichorium extract (200, 400 and 600 mg/kg body weight) were investigated to determine the significant effective dose against colorectal cancer using differential display-PCR (DD-PCR), DNA sequencing, histopathological and cytological techniques. The results showed that the cichorium extract dose 200 mg/kg body weight was the best one compared to the others (400 and 600 mg/kg body weight). This finding could be a powerful therapeutic against colorectal cancer.